Participative Management: A Key to Success in Colleges of Agriculture and Technology: Participative Management: A Key to Success in Colleges of Agriculture and Technology - Yotha, Suriya; Phitaphan, Chettha; Namnaphon, Surin; Tonwut, Phanupong (RATANABUTH JOURNAL, 2026)
This academic article aimed to analyze the role of participatory management as a key factor contributing to the success of Colleges of Agriculture and Technology, as well as to examine the integration of the Buddhist principle of Iddhipāda 4 with modern management concepts in order to enhance the effectiveness and sustainability of educational organizations. The study of related research and documents found that participatory management served as an important mechanism for promoting collaboration, shared decision-making, and organizational commitment among personnel. It provided opportunities for teachers, staff, students, and external stakeholders, including enterprises and local communities, to participate in determining the developmental direction of educational institutions. As a result, educational management and curriculum development became more consistent with socio-economic contexts and the demands of the modern labor market. The findings also revealed that although many educational institutions had adopted participatory management approaches, their implementation often reflected “symbolic participation” rather than genuine involvement. Consequently, organizational development had not fully achieved sustainability and effectiveness. Therefore, the application of the Buddhist principle of Iddhipāda 4, consisting of Chanda (satisfaction), Viriya (perseverance), Citta (attentiveness), and Vimamsa (investigation), was regarded as an essential approach for fostering motivation, responsibility, and commitment among personnel. These principles contributed to meaningful participation and systematic organizational development.